The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.21203/rs.3.rs-1407540/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacterial and Fungal Isolation from Face Masks: Newly Emerged Hygiene Issues Under COVID-19 Pandemic

Abstract: The COVID-19 pandemic has led people to wear face masks daily in public. Although the effectiveness of the face masks against viral transmission has been extensively studied, there is no report on potential hygiene issues due to bacteria and fungi attached to the face masks. We aimed to demonstrate 1, information of the usage duration and types of masks; 2, the number of bacteria and fungi attaching to masks; and 3, identification of the bacteria and fungi attaching to masks. We conducted a survey of 109 volun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The oral cavity has various microhabitats, including tongue bio lms, teeth, subgingival uid, dental plaque, and saliva, and the microorganism pro le and amounts differ depending on where it is sampled 23,28 . In a recent COVID-19 mask study, the number of bacterial colonies was greater on the face than on the outer-side [29] 29 . This is probably because different bacteria have different shapes, metabolisms, surface adhesion, and survival strategies.…”
Section: Discussionmentioning
confidence: 88%
“…The oral cavity has various microhabitats, including tongue bio lms, teeth, subgingival uid, dental plaque, and saliva, and the microorganism pro le and amounts differ depending on where it is sampled 23,28 . In a recent COVID-19 mask study, the number of bacterial colonies was greater on the face than on the outer-side [29] 29 . This is probably because different bacteria have different shapes, metabolisms, surface adhesion, and survival strategies.…”
Section: Discussionmentioning
confidence: 88%
“…Contamination of the mask due to wearing for the prolonged period should also be considered. Park reported the result of culturing bacteria and fungi from outer and inner layers of the masks wore by 109 Japanese people, and it was found that the mean colony counts were 13.4-times higher on the face-side of masks ( 83 ). To sum up, the effectiveness of masks, especially universal masking, seems to be limited based on the evidence described above.…”
Section: Mask Rules (Mandate): Review Of Its Effectivenessmentioning
confidence: 99%
“…Equipped with corresponding technical support equipment, it can meet different needs, such as inspection, screening, treatment and isolation. However, it is limited in use when encountering extreme weather conditions, such as storms [ 2 ]. The operation environment of the field shelter hospital is stable and good, but the delivery process depends on large vehicles.…”
Section: Introductionmentioning
confidence: 99%